2007
DOI: 10.1177/1934578x0700201218
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Cytotoxic Activity ofNepeta CatariaL., N. Cataria Var. Citriodora (Beck.) Balb. andMelissa OfficinalisL. Essential Oils

Abstract: The aim of the present study was to investigate the susceptibility of bacteria that play a role in respiratory tract and skin infections to the essential oils of catnip (Nepeta cataria), lemon catnip (N. cataria var. citriodora) and lemon balm (Melissa officinalis) with regard to their chemical composition. In addition, we wanted to assess whether antibiotic-resistant and-sensitive strains differ in their susceptibility to the oils and if there are cross resistances between standard antibiotics and essential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 45 publications
0
25
2
Order By: Relevance
“…It was found that nepetalactones were responsible for the feline attractant properties of Nepeta species. 4aα,7α,7aα-Nepetalactone, which was the main component of our oil, has been detected as the major one in four Nepeta species growing in Turkey [21] and also in N. cataria growing in Germany [22], while caryophyllene oxide, which was abundant in N. cataria from Lebanon [23] and Lithuania [24] (6.4%, 7.3% respectively), was not found in our work. β-Caryophyllene, which was the third major component of our oil, has been reported in the oil of some Nepeta species such as N. cataria [23], N. daenensis [25], and N. fissa from Iran [26], and in N. curviflora growing in Lebanon [23].…”
contrasting
confidence: 81%
“…It was found that nepetalactones were responsible for the feline attractant properties of Nepeta species. 4aα,7α,7aα-Nepetalactone, which was the main component of our oil, has been detected as the major one in four Nepeta species growing in Turkey [21] and also in N. cataria growing in Germany [22], while caryophyllene oxide, which was abundant in N. cataria from Lebanon [23] and Lithuania [24] (6.4%, 7.3% respectively), was not found in our work. β-Caryophyllene, which was the third major component of our oil, has been reported in the oil of some Nepeta species such as N. cataria [23], N. daenensis [25], and N. fissa from Iran [26], and in N. curviflora growing in Lebanon [23].…”
contrasting
confidence: 81%
“…9 The essential oil composition and antimicrobial activity of various Nepeta species were previously reported. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] In earlier communications, some Himalayan Nepeta species were screened for their terpenoid constituents. 18-23 Iridodial β-monoenol acetate isolated from essential oil of N. leucophylla Benth.…”
Section: Introductionmentioning
confidence: 99%
“…The oil extracted from lemon balm leaves and herb contains citral (responsible for the characteristic lemon scent of the leaves), linalool, citronellal, neral, and geranial [5][6][7][8][9][10][11]. Lemon balm oil has refreshing, sedative, antidepressant [12], antimicrobial [13,14], antidiabetic [15], antioxidant and antitumor properties [16,17]. The chemical composition of lemon balm oil shows high variability and depends, amongst others, on plant origin [6,9,18] and cultivation conditions [3,7,19,20].…”
mentioning
confidence: 99%